2019
DOI: 10.1097/md.0000000000016559
|View full text |Cite
|
Sign up to set email alerts
|

The risk factors of nonunion after intramedullary nailing fixation of femur shaft fracture in middle age patients

Abstract: Although the optimal treatment for femur shaft fracture is intramedullary nailing fixation, nonunion still occurs. We determined the oligotrophic nonunion rate among femur fractures managed operatively and identified risk factors for reoperation. This was a retrospective clinical study. The data of the patients between 40 and 70 years old with diaphyseal femur fracture who have received reamed and interlocked intramedullary nailing fixation in our hospital from February 2014 to April 2018 were collected. They … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 19 publications
1
36
0
1
Order By: Relevance
“…The included studies were designed as follows: one was prospective ( 14 ), one was uncertain ( 15 ), and the remaining 28 were retrospective ( 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ) ( Table 1 ). The studies included 38 465 patients, of which 3,975 suffered from nonunion.…”
Section: Resultsmentioning
confidence: 99%
“…The included studies were designed as follows: one was prospective ( 14 ), one was uncertain ( 15 ), and the remaining 28 were retrospective ( 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ) ( Table 1 ). The studies included 38 465 patients, of which 3,975 suffered from nonunion.…”
Section: Resultsmentioning
confidence: 99%
“…In general, the factors identified can be classified into four categories: patient-related factors, environment factors, injury-related factors, and surgery-related factors. Wu et al reported that fracture site comminution; fracture at the proximal third junction; and comorbidities such as obesity, hypertension, and diabetes mellitus were associated with a higher risk of nonunion [ 23 ]. A systematic review conducted by Santolini et al highlighted 10 risk factors for long bone fracture nonunion [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ten of these type B femur fractures went on to delayed union (defined as the absence of union after three months) and were either treated with nail dynamization or went on to union without intervention. There are various risk factors that increase the risk for nonunion, including obesity, hypertension, diabetes, fracture site at the proximal third of the femur, or a comminuted fracture pattern [ 8 - 9 ]. In addition to nonunion, another potential complication is the penetration of the femoral anterior cortex intraoperatively; several studies have explored the risk factors and prevention of this issue [ 1 - 4 ].…”
Section: Discussionmentioning
confidence: 99%